Adsorption at Natural Minerals/Water Interfaces - Song, Shaoxian; Li, Bowen (Springer International Publishing, 2021)
This book introduces the latest research regarding the adsorption of heavy metals, toxic ions, and organic compounds at the interfaces of water/minerals, such as mineralogical characterizations, surface chemistry, and modification of natural minerals as adsorbents, as well as the adsorption of cations, anions, and organic compounds in water. Presenting findings by the authors and their co-workers, the book helps readers grasp the principals and benefits of using minerals for water treatment, as well as the advanced technologies in the area developed over last 30 years, especially the last 10 years.
Mineral Adsorbents and Characteristics -- Surface Chemistry of Mineral Adsorbents -- Modification of Mineral Surfaces and Microstructures -- Adsorption of Minerals to Anions -- Adsorption of Minerals to Cations -- Adsorption of Minerals to Organic Compounds -- Bioadsorption of Minerals.-Contaminated Water Treatment -- Dewatering of Mineral Adsorbents
Keywords: Materials science; Water; Green chemistry; Mineral resources; Adsorption; Mineral; Schwermetall; Aufsatzsammlung